Antibacterial Hydrogel Films Embedded with Cu–Ag Oxide Nanoparticles Based on Basil Seed Mucilage for Advanced Wound Dressing Applications - Sripirom, Jiyapa; Srisomang, Rungrudee; Siri-Udom , Sakuntala; Morales Futalan, Cybelle; Prasitnok, Khongvit; Prasitnok, Orrasa; Kamonwannasit, Sirilak; Kamcharoen, Agarat; Khemthong, Pongtanawat; Phatai, Piaw (Trends in Sciences, 2025)
Hydrogel films with antibacterial properties, swelling capability, and mechanical strength show promise as wound dressings. This study investigates the fabrication of Cu1.0-xAgₓO (x = 0.0, 0.1, 0.5, 0.9, and 1.0) antibacterial nanoparticles loaded into basil seed mucilage (BSM)/hydrogel (BSM/HG) films via a casting method. The crystal phases, surface chemical composition, and antimicrobial efficacy of Cu1.0-xAgₓO particles were characterized using X-ray diffraction (XRD), X-ray photoemission spectroscopy (XPS), and agar well diffusion assays. XRD analysis confirmed that Cu1.0-xAgₓO (x = 0.1 – 0.7) samples formed composites containing CuO, Ag, and Ag2O phases. Among them, Cu0.7Ag0.3O exhibited superior antibacterial activity, achieving inhibition zone diameters of 8 - 13 mm against Bacillus cereus, Staphylococcus aureus, Streptococcus thermophilus, and Escherichia coli. The hydrogel demonstrated good swelling capacity and mechanical strength suitable for wound dressing applications. The incorporation of Cu0.7Ag0.3O nanoparticles into BSM/HG films reduced both swelling capacity and tensile strength due to particle agglomeration, although the antibacterial properties were significantly enhanced. This research highlights the potential of Cu1.0-xAgₓO-loaded BSM/HG films for advanced wound dressing applications. HIGHLIGHTS Formation of various phases on Cu0.7Ag0.3O composite including CuO, metallic Ag and Ag2O improved antibacterial activity. Cu0.7Ag0.3O loaded BSM/HG film showed excellent antibacterial activity against Gram-positive and Gram-negative bacteria. Cu0.7Ag0.3O loaded BSM/HG film has the suitability as an antibacterial material in biomedical applications. GRAPHICAL ABSTRACT